2021
DOI: 10.1080/00036846.2020.1870921
|View full text |Cite
|
Sign up to set email alerts
|

Does listed real estate behave like direct real estate? Updated and broader evidence

Abstract: This study investigates a question relevant to many investors: do the broad Real Estate Investment Trust (REIT) return characteristics reflect those of the broad direct real estate markets. The paper makes several contributions to the literature in addition to using more recent data: (1) we use data for six countries (Australia, France, Germany, Netherlands, the U.K., and the U.S.); (2) we estimate both country-specific and panel models to increase the reliability and generalizability of the analysis; (3) we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…We first look at the behavior of securitized real estate capital returns across sectors in Europe. Such analysis is useful as research has shown that, given its greater information efficiency, the listed real estate market reacts more quickly to changes in fundamentals than the direct market (Hoesli and Oikarinen, 2012, 2021). Hence, the listed real estate market should uncover any price developments before the direct market.…”
Section: Real Estate Prices Post-covid-19mentioning
confidence: 99%
“…We first look at the behavior of securitized real estate capital returns across sectors in Europe. Such analysis is useful as research has shown that, given its greater information efficiency, the listed real estate market reacts more quickly to changes in fundamentals than the direct market (Hoesli and Oikarinen, 2012, 2021). Hence, the listed real estate market should uncover any price developments before the direct market.…”
Section: Real Estate Prices Post-covid-19mentioning
confidence: 99%
“…alternatywnych nieruchomości, jak centra obsługi danych (EPRA, 202b). Porównując długoterminowe zyski z notowanych i nienotowanych spółek nieruchomościowych opartych na tych samych aktywach bazowych, widzimy, że sektor giełdowy jest efektywnym wskaźnikiem zastępczym dla bezpośrednich inwestycji w nieruchomości (Hoesli i Oikarinen, 2021). Jednak podmioty inwestujące w nieruchomości notowane na giełdzie -jak REIT (LRE) -mają tę zaletę, że są bardziej przejrzyste, dywersyfikowane, płynne i oferują łatwiejszy globalny dostęp do nieruchomości w porównaniu z typowymi inwestycjami bezpośrednimi (EPRA, 2020a).…”
Section: Działalność Podmiotów Typu Reit a Covid-19unclassified